Wonder Woman, earth one. Volume 2 - Morrison, Grant (DC Comics, 2018)
"For years, Diana of Paradise Island yearned to leave the only home she knew behind for adventures that laid beyond its shores. Now, after a fateful meeting with Air Force pilot Steve Trevor, the Amazon Warrior finds herself in Man's World. And she is ready for anything that it may throw at her. But is the world ready for Wonder Woman? An American Government, fraught with dissession and conflicts foreign to Diana, have deemed her a danger to society. How will Wonder Woman carry out her mission of peace and love in a world that can't get out of its own way? That is, unless there are more insidious forces at play..."--Back cover.